Thematic analysis of self-experience, cultural expression and islamic expression on Haron Mokhtar’s series of paintings / Alif Haiqal Musa and May Tasneem Nor Adzaman - Alif Haiqal, Musa; May Tasneem, Nor Adzaman (Universiti Teknologi MARA, Perak, 2020)
Haron Mokhtar has begun his career as an artist since 1980s and became popular Award in the Bakat Muda Sezaman at National Visual Arts Gallery (BSLN) in 1987 and been awarded an Anugerah Darjah Kebesaran Setia Mahkota Selangor Yang Amat Mulia (2014). However, the documentations about his works are still lack. Thus, this research paper conducted to documenting the themes that used by Haron Mokhtar’s in creating artwork. A close observation towards all the eight (8) series of Haron Mokhtar’s paintings was conducted in order to analyze and identify the themes of the paintings. Those series of paintings are ‘Siri Kaseh Sayang’ (1995), In Persuit of Penang (1999), ‘Siri Atas Bawah Pusaka’ (2005), ‘Siri Sutera Mengadap Tuanku Sultan’ (2009), ‘Siri Warisan’ (2011), ‘Siri Dari Kulaan Studio ke Istana Mestika’ (2012-2014), Yesteryears Series (2015) and ‘Siri Perakam Waktu” (2018). From the analysis, researcher has come up with three (3) main themes which are Self-Expression, Cultural Expression and Islamic Expression. All the themes applied by the artist have put his painting on high demand for both locally and abroad